Menggali Motivasi, Faktor yang Mempengaruhi, dan Hambatan Pustakawan dalam Mengikuti Call for Paper atau Call for Best Practice - Hana Isnaini Al Husna (Universitas Sebelas Maret Library, 2024)
This research is qualitative research with case studies, using ERG (Existence, Relatedness, Growth) theory to analyze the motivation of librarians in following the call for paper (CFP) and call for best practice (CFBP). This study aims to determine the motivations, factors, and obstacles librarians face when participating in these activities. The results showed that 13 librarians had experience participating in CFP and CFBP activities. Librarian motivation has fulfilled the ERG motivation theory. The Existence category includes the existence and welfare of institutions and the profession's demands. The Relatedness category includes networking and knowledge sharing, while the Growth category includes self-actualization, achievement, rewards, and competency development. Factors that influence librarian motivation include internal factors such as self-development, love to write and try new things, increased experience, self-satisfaction, and existence. External factors include performance for the fulfillment of credit and portfolio figures, library accreditation, promotion of institutions, getting welfare from institutions, competitions, friend invitations, and the theme and location of seminars. However, librarians face several obstacles, such as limited time, funding, licensing bureaucracy, difficulty finding writing partners, finding references, lack of confidence, nervousness during presentations, and lack of enthusiasm for writing. This research provides valuable insights for the professional development of librarians and increases their participation in scholarly activities. It is expected that librarians will be more active in participating in scientific activities to increase the productivity of scientific work that impacts themselves and institutions.